Two Centuries of Russian Sámi Policy: Arrangements for Autonomy and Participation Seen in Light of Imperial, Soviet and Federal Indigenous Minority Policy 1822–2014 - Berg-Nordlie, Mikkel (Acta Borealia, 2015)
This article reviews arrangements for Russian Sámi self-government during the Late Imperial (1822–1917), Soviet (1917–1991) and Federal (1992–) Eras of Russian history, comparing them to developments in the country's general indigenous minority policy. Since the Soviet Era, indigenous minority policy has been delimited to a subset of the country's actual indigenous nations – smaller groups traditionally involved in certain rural economic activities. State paternalism, the framing of indigenous minority policy as giving aid to weak groups, is a constant trait of Russian indigenous minority policy. This paternalism has been channelled towards different goals at different times – the building of Communist nations, assimilation, or traditionalist preservationism. Indigenous minority policy has generally been weakly institutionalized, and its interests come into conflict with stronger actors who anchor their political activity in northern economic development and state security. Different forms of territorial autonomy have been practiced throughout the period, non-territorial arrangements becoming more common only in the Federal Era. Russian Sámi politics generally match the national trends but are a case of particularly weak indigenous autonomy and participation. A very case-specific phenomenon is the Federal Era conflict over whether or not to import the Nordic Sámi Parliament model. Case-specifics are explained by the weak demographic position of the Russian Sámi, the lack of any significant symbolic connection between the province and its indigenous people, and the border-proximity and border-transcendence of the Sámi people, which has repeatedly been used to frame their activism as a security concern. Published in Taylor and Francis Journal. 18-month embargo. Article available here http://www.tandfonline.com/doi/full/10.1080/08003831.2015.1030849